The Effectiveness of Cognitive Behavior Therapy Group Conseling Cognitive with Cognitive Restructuring and Thought Stopping Techniques to Reduce Students Consumptive Behavior (Jurnal Bimbingan Konseling, 2018)
This study aimed to determine the effectiveness of cognitive behavior therapy group counseling with cognitive restructuring and thought stopping techniques to reduce students' consumptive behavior. This experimental study used a pretest posttest group design by involving 14 students of Vocational High School (SMK) Bhakti Nusantara Boja as the members of cognitive restructuring technique group (7 students) and thought stopping technique group (7 students). The results of data analysis using Wilcoxon and Mann-Whitney tests showed that cognitive behavior therapy group counseling with cognitive restructuring and thought stopping techniques was effective in reducing students' consumptive behavior. The discussion of the results of this study was directed to reinforce the effectiveness of cognitive behavior therapy group counseling with cognitive restructuring and thought stopping techniques to reduce students’ consumptive behavior.